RESPONS NEGARA AUSTRALIA TERHADAP KEMERDEKAAN INDONESIA MELALUI BLACK ARMADA DAN FILM DOKUMENTER INDONESIA CALLING - Ardi Tri Yuwono (Prabayaksa: Journal of History Education, 2025)
The recognition of sovereignty to a country by another country is one of the conditions for the establishment of a country, including the Republic of Indonesia which has just proclaimed independence on August 17, 1945. One of the countries that supported and recognized the existence of Indonesia at that time was Australia. Australia at that time supported Indonesian Independence through a union strike against Dutch ships in Australian ports that wanted to sail back to Indonesia in order to reclaim their colony. This strike action is known as Black Armada  and is documented through the documentary film Indonesia Calling. The purpose of this research is to understand the memory contained in the documentary film Indonesia Calling and its correlation with the Black Armada event. The research uses historical methods with a qualitative approach. The Black Armada  incident occurred for four years (1945-1949) which was marked by a strike by Indonesian shipworkers. In subsequent developments, the strike spread across Australia and was followed by ship workers union and Australian citizen, particularly in Sydney, Melbourne, Brisbane and Fremantle. This action was documented through the film Indonesia Calling by Joris Ivens which was then disseminated to the international world so that other countries provided support for Indonesian independence as a condition for the establishment of a country.